Akceptacja i polemika tłumaczeniowa w interpretacji literackich nazw własnych. Na przykładzie rosyjskiego i polskiego przekładu sagi o Harrym Potterze - Rachut, Konrad (Studia Rossica Posnaniensia, 2016)
Translation of literary proper names boils down to either accurately rendering their original form / meaning or finding equivalents which have less in common with their original versions. In the article the author attempts to deduce what might have caused the translators to choose one of the two strategies by means of analysing chosen examples from the saga. Apparently, the translators’ decisions stem not only from the limitations of respective languages and cultures, but also from their individual approach towards the original text.